Warriors. Winds of change - Jolley, Dan; Hunter, Erin (Harper Alley, an imprint of HarperCollinsPublishers, 2020)
"After a treacherous journey, the warrior Clans have begun to settle into their new homes around the lake. But while some cats see their new beginning as a chance to build a lasting peace, WindClan's deputy Mudclaw believes the other Clans cannot be trusted. And as he prepares to take the ailing Tallstar's place as leader, Mudclaw will do whatever it takes to secure the future of his Clan--no matter who stands in his way"--Back cover.